In vitro conservation and distribution of root and tuber crop germplasm - Ng, S.Y.C. (1991)
The in vitro methods that can be used or are in use in root crop germplasm conservation and distribution are described, namely (1) normal growth storage, (2) reduced growth storage (reduced incubation temp., manipulation of culture media, both of the former), and (3) cryopreservation. The achievements of applying some of these methods are summarized and the advantages of using tissue culture materials in germplasm exchange are highlighted. In the case of reduced incubation temp. for cassava, node explants are stored in plantlet culture type at either 20 degrees C for 18-24 mo. or in liquid media with filter paper bridge incubated at 20 degrees C and with a 16-h photoperiod with 100-200 lux light intensity. When culture media were manipulated, cassava node explants are used in plantlet culture type and stored for 2 yr in large culture vessels, with culture media containing low osmotic concn. and activated charcoal